English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can u help me with this?

x^2(x squared) - 6xy + 8y^2(8y squared) = ?

2006-11-10 15:50:17 · 6 answers · asked by double B 2 in Science & Mathematics Mathematics

6 answers

x^2-6xy+8y^2
x^2-6xy+9y^2-9y^2+8y^2
(x-3y)^2-y^2
(x-3y+y)(x-3y-y)
(x-2y)(x-4y)

aliter
x^2-4xy-2xy+8y^2
x(x-4y)-2y(x-4y)
(x-4y)(x-2y)

2006-11-10 15:56:44 · answer #1 · answered by raj 7 · 0 0

x^2 - 6xy + 8y^2 =
This binomial factors in much the same way as a single-variable function:
some sum of factors of 8 must equal 6. Both will be negative, since 8 is positive.
1 + 8 = 9
2 + 4 = 6, Aha!
your factors are then
(x - 2y)(x - 4y)

2006-11-10 23:58:48 · answer #2 · answered by Helmut 7 · 0 0

Start off by knowing x(x) = x^2 and y(y) = y^2.

Plug it in (x _y)(x _y)

Now ask yourself, what two numbers multiply to be 8 and add to be -6.

You find (-4)(-2) = 8 and (-4) + (-2) = -6

So,

(x - 4y)(x - 2y) = x^2 - 6xy + 8y^2

2006-11-10 23:58:39 · answer #3 · answered by MB 2 · 0 0

try to complete the square
x^2 - 6xy + (3y)^2 - (3y)^2 +8y^2
= (x - 3y)^2 - y^2
=(x - 3y -y)(x - 3y + y)
=(x -4y)(x - 2y)

2006-11-11 00:04:48 · answer #4 · answered by Anonymous · 0 0

(x-2y)(x-4y)

2006-11-11 00:06:10 · answer #5 · answered by J 6 · 0 0

(x-2y)(x-4y)

2006-11-10 23:57:59 · answer #6 · answered by onelove92901 3 · 0 0

fedest.com, questions and answers